PENELITIAN BERBAGAI JENIS KAYU LIMBAH PENGOLAHAN UNTUK PEMILIHAN BAHAN BAKU BRIKET ARANG - Malik, Usman (2302-0792, 2013)
The waste of timber industry can be utilized to producesome valuable products. A research had been conducted tostudy such possibility. The research was to study the conversionof wood into charcoal briquetting using adhesive or heatingprocess. Result showed that the heating value of charcoalbriquetting made from kempas wood (koompassia malaccensismaing), meranti (shorea spp.) and pulai (alstonia spp)increases significantly compared to that of raw material. Theproduct made from kempas wood (koompassia malaccensismaing.) was formed to have the highest energy per cc (density)followed by those of made of meranti (shorea spp.), ramin(gonystylus bancanus kurz.). However, raw materialavailability must be consideret in establishing charcoalbriquetting industry.